The Use of Picture Series Technique to Improve Students’ Writing Skills on Recount Text to the Eighth Grade Students at SMP N 6 Tabanan - NI PUTU AYU KARTIKA SARI DEWI; I Made Suamba; AA Sagung Inten Liana Pramesuari (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2022)
This research aims to improve students' writing skills in recount text using the picture series technique. The subjects were the eighth grade students at SMP N 6 Tabanan in the academic year 2021/2022. Consisting of 29 eighth students. This research was categorized as Classroom Action Research (CAR). Data were collected by conducting observations, documentation and tests. The research was conducted in two cycles in which each cycle consists of planning, action, observation, and reflection. The result of this research after the implementation of the picture series technique showed that students seemed more confident when writing and began to generate ideas for writing texts. It can be proven by comparing the average value of each score from pre-test to post-test. In the pre-test the average score obtained by students was 47.06%. After the application of the picture series in cycle I the average value was 65.52%. Meanwhile, the results of the post-test of students in cycle II reached 80.86%. With these results, it can be concluded that the picture series technique can improve students’ learning outcomes and can be applied in the teaching and learning process, especially for writing.